Common fixed points and invariant approximation of R-subweakly commuting maps in convex metric spaces - Narang, T.D.; Chandok, S. (Український математичний журнал, 2010)
Sufficient conditions for the existence of a common fixed point of R-subweakly commuting mappings are established within the framework of a convex metric space. As applications, we obtain various results on the best approximation for this class of mappings generalizing the results known from the literature. Встановлено достатні умови існування спільної нерухомої точки R-субслабко комутуючих відображень у рамках опуклого метричного простору. Як застосування, одержано різні результати щодо найкращих наближень для згаданого класу відображень, які узагальнюють інші відомі з літератури результати.